سورة المنافقين دراسة تحليلية - محمد الطاهر, عبايدي; عبد الواحد, مهاوات; عماد الدين, مهاوات (جامعة الوادي university of eloued, 2014)
Dealt Sura stones to start ethics hypocrites, and their qualities reprehensible that shown lying, and contrary apparent soles, they say with their tongues what is not you think their hearts, and then plotting and Muslims, has Vdanhm sura revealed Mkhazém and freshthe Prophet crimes, they are pretending to Islam, deterring people from the religion of God and attain the call of Islam is not bestowed infidels declared infidels, and so was their danger greatest, and Dhararham the largest and most serious, also spoke Sura stones for their articles , and believed that his callheinous in the right of the Prophet Stdmahl and fade, and after they return from "Banu Mustaliq" will be expelled Prophet and the believers of Medina, and concluded by warning the faithful that engage adornment minimum and Hoha and pleasures for obedience to God and worship like the hypocrites, and showed that by losers, and is spending for the sake of God in order to please God, before it is too late end of the term, Vihsr rights and regret where served anguish and remorse.